Practical continuous-variable quantum secret sharing using local local oscillator - Qin Liao; Zhuoying Fei; Lei Huang; Xiquan Fu (Communications Physics)
Abstract Although continuous-variable quantum secret sharing (CVQSS) has been theoretically proven to be secure, it may still be vulnerable to various local oscillator (LO) attacks. To close this loophole, here we propose a practical CVQSS scheme using local LO (LLO-CVQSS), where LO is no longer generated by each user but is locally generated by the legitimate dealer. This waives the necessity that all LOs have to be transmitted through untrusted channels, making CVQSS system naturally immune to all LO-aimed attacks and enhancing its practical security. We also develop a dedicated phase compensation method for LLO-CVQSS to control the phase noise, and construct a noise model that derives its security bound against both eavesdroppers and dishonest users. Finally, numerical simulation shows that LLO-CVQSS can support 30 users at the same time and the maximal transmission distance reaches 112 km, revealing its potential for building large-scale practical quantum communication networks.